1997
DOI: 10.1046/j.1360-0443.1997.9289797.x
|View full text |Cite
|
Sign up to set email alerts
|

The Self-Rating of the Effects of Alcohol (SRE) form as a retrospective measure of the risk for alcoholism

Abstract: When alcohol challenges are not possible, these retrospective reports indicate that the SRE is a potentially useful surrogate for determining a subgroup of people who might carry a low level of response to alcohol and a subsequent elevated risk for alcoholism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
151
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(156 citation statements)
references
References 0 publications
4
151
1
Order By: Relevance
“…Lower levels of response to alcohol are indicated by higher overall scores on the SRE. Consistent with previous reports, low responders were defined as those who had a total SRE score of 4.5 or higher (Schuckit et al, 1997a(Schuckit et al, , 1997bWall et al, 1999).…”
Section: Methods Proceduresmentioning
confidence: 61%
See 1 more Smart Citation
“…Lower levels of response to alcohol are indicated by higher overall scores on the SRE. Consistent with previous reports, low responders were defined as those who had a total SRE score of 4.5 or higher (Schuckit et al, 1997a(Schuckit et al, , 1997bWall et al, 1999).…”
Section: Methods Proceduresmentioning
confidence: 61%
“…Higher scores on the SRE indicate that more drinks are required to have an effect, implying a lower level of response per drink. SRE values have correlated with data from alcohol challenge studies at about 0.4 to 0.6 (Schuckit et al, 1997a(Schuckit et al, , 1997b and have correlated with the ALDH2*2 allele at 0.35 .…”
mentioning
confidence: 84%
“…When parent and offspring disagreed, the worst-case scenario (e.g., higher number of alcohol problems) was used in the analyses. Those offspring who at T25 reported drinking on their own on multiple occasions were asked to fi ll out the SRE regarding the approximate fi rst fi ve times of drinking (Schuckit et al, 1997a(Schuckit et al, , b, 2007. At T25, subjects reported the number of standard drinks (~10 g of ethanol) required to fi rst feel the effects of alcohol, the drinks needed to produce slurring of speech, the alcohol required to feel unsteady or uncoordinated, and the amount of alcohol ingested before unwanted falling asleep (passing out), taking care to report only the drinks required for actual effects experienced.…”
Section: Methodsmentioning
confidence: 99%
“…First, a recent study of almost 300 Swiss men and women at an average age of 43 years reported a relative risk of alcohol dependence that was 4.4 times higher among subjects whose FIRST 5 SRE scores fell into the lowest third compared with those whose scores were in the upper third (Daeppen et al, 2000). Second, a follow-up of almost 100 young adult subjects in the United States demonstrated a correlation of approximately 0.4 for various measures on the SRE and the diagnosis of alcohol dependence, with correlations as high as 0.6 in a more heterogeneous sample of more than 500 men and women from a wide range of ages (Schuckit et al, 1997a). Finally, SRE scores also correlated with alcohol metabolizing enzyme patterns in the predicted direction among Asian men and women, with lower LRs among individuals with the more efficient aldehyde dehydrogenase isoenzyme pattern known to be associated with a higher alcoholism risk through more intense and possibly more aversive reactions to alcohol .…”
mentioning
confidence: 99%